Analysis of Traffic Accidents Due to Road Damage - Surodjo; Vicki Dwi Purnomo; Syukron Abdul Kadir; Benedictus Hestu Cipto Handoyo (Formosa Journal of Multidisciplinary Research, 2023)
The traffic space has road infrastructure which is the main need for the community as transportation access which is important in carrying out activities and daily needs. has been regulated by Law No. 22 of 2009 concerning Road Traffic and Transportation. The obligation to maintain roads has been regulated in Article 24 of the LLAJ Law and criminal sanctions in Article 273 of the LLAJ Law. Accidents caused by damaged roads occur quite often, but they are still common in society so that accident victims report their losses to the authorities so it is not uncommon to find cases that have advanced to court. This paper aims to find out how law enforcement is against road administrators who are negligent and what factors are the obstacles. case (case approach), while the data sources used are secondary data sources, data collection techniques through library research, and analyzed by qualitative analysis.